Virtual reality training and pain neuroscience plus motor control on pain, disability, health, and quality of life of women with non-specific chronic back pain - Ensiye Reza; Rafael Oliveira; Behrooz Sarvari Far; Faeze Molaee; Hadi Mohammadi Nia Samakosh (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2024)
Background: Non-specific chronic low back pain is defined as a complex disorder involving structural, biomechanical, cognitive, psychological, social, and lifestyle factors. This randomized clinical trial study compared the effects of 8-week Virtual Reality Training (VRT) and pain neuroscience plus motor control training (PNE/MCT) on pain, disability, health, and quality of life of women with non-specific chronic back pain. Methodology: This research is a single-center parallel RCT. Thirty-six participants participated in this study. They were divided into two groups: VRT (G1) and PNE/MCT (G2), both with 18 women. The training was performed for eight weeks for 45 minutes - 60 minutes. The VRT was applied by Oculus Quest 2. Visual Analogue Scale (VAS), disability (Oswestry Disability Index), general health (GHQ-28), and quality of life (QOL- WHO) were assessed before and after eight training weeks using a within-between group analysis (ANOVA 2×2). Results: Before training, no difference was observed between the groups (p > 0.05). After the intervention, both groups improved VAS, disability, GHQ, and QOL (all p < 0.001). In the comparison between the groups, the G1 had a better performance according to the p-value and effect size in anxiety (p = 0.001, ES= 0.71), depression symptoms (p = 0.03, ES: 0.25), physical health (p = 0.03, ES: -0.24), mental health (p = 0.001, ES: 0.66), and total QOL (p = 0.048, ES: 0.21) than G2. Conclusion: Despite the effectiveness of both interventions, VRT improved the general health and quality of life in women with NSCLBP more than PNE/MCT.